MANAGEMENT OF MRTS USING THE METHOD OF POTENTIALS IN AN INTERFERING ENVIRONMENT - Колумбет, Вадим (SWorldJournal, 2021)
In this hour, all the greater relevance is developing multi-agent robotic systems (MRTS), as there are wider resources in industrial areas, the sphere of service, as well as those who are involved in traveling with people. One of the most common problems